Regulation of BACE1 by miR-29a/b in a cellular model of spinocerebellar ataxia 17 - Roshan, Reema; Ghosh, Tanay; Gadgil, Mugdha; Pillai, Beena (RNA Biology, 2012)
Polyglutamine diseases are a class of neurodegenerative disorders characterized by expansion of polyglutamine repeats, protein aggregation and neuronal cell death in specific regions of the brain. The expansion of a polyglutamine repeat in the TATA binding protein (TBP) causes a neurodegenerative disease, Spinocerebellar Ataxia 17 (SC A17). This disease is characterized by intranuclear protein aggregates and selective loss of cerebellar neurons, including Purkinje cells. MicroRNAs are small, endogenous, regulatory non-coding RNA molecules that bind to mRNAs with partial complementarity and interfere in their expression. Here, we used a cellular model of SC A17 where we expressed TBP with 16 (normal) or 59 (pathogenic) polyglutamines and found differential expression of several microRNAs. Specifically, we found two microRNAs, miR-29a/b, were downregulated. With miR-29a/b downregulation, we found an increased expression of targets of miR-29a/b-beta-site amyloid precursor protein cleaving enzyme 1 (BACE 1), p53 upregulated modulator of apoptosis (PUMA) and BAK, increased cytochrome c release and apoptosis. Restoration of miR-29a/b in the pathogenic polyglutamine background reduced the BACE 1 expression. While, antagomiRs against miR-29a/b resulted in an increase in BACE 1 levels and neuronal apoptosis. In spite of the elevation of BACE 1 in Alzhemiers disease, its role in neuronal cell death has not been established. Here, we show that increased BACE 1 expression is not sufficient to cause apoptosis. However restoring level of BACE 1 to normal in polyglutamine cells partially reduced neuronal apoptosis. We show a role for the miR-29a/b-BACE 1 regulatory interaction in SC A17, suggesting that this microRNA could be part of a common molecular mechanism leading to neuronal cell death in multiple neurodegenerative disorders. The identification of a common mechanism of microRNA mediated neurodegeneration not only improves our understanding of the process, but also provides promising and novel therapeutic targets.
Keywords: BACE1; miR-29a/b; neurodegeneration; SCA17; TBP